Strategi Digitalisasi di Bank Syariah untuk Meningkatkan Daya Saing - Setiawan, Aji; Diadani, Prans Sintia; Masyita, Rilla; Putri, S Ritonga Ari; Nurbaiti, Nurbaiti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Digitalization strategies in Islamic banks are important to increase competitiveness in the increasingly competitive digital era. The research objective of this journal is to explore the development and strategies of digitization in Islamic banks in an effort to improve their competitiveness in the increasingly growing digital era. With the advancement of financial technology and changes in consumer behaviour, Islamic banks are faced with the challenge of providing faster, easier, and more accessible services, while still complying with sharia principles. This research uses a qualitative approach with the literature study method to collect relevant data and information regarding digitalization in sharia banking. Research results show that the implementation of sharia financial technology, the development of digital banking platforms, the use of Big Data, and the implementation of blockchain are key strategies that can increase the competitiveness of Islamic banks. The implementation of sharia fintech can expand access to banking services and attract young customers, while digital platforms such as mobile banking and internet banking can facilitate transactions. In addition, the use of Big Data allows banks to understand customer behaviours and offer more personalized services, while blockchain increases transaction security and transparency. In conclusion, digitalization is not only an option, but a necessity for Islamic banks to remain relevant and compete in the increasingly dynamic financial market.